Parametric Modeling as an Alternative Tool for Planning and Management of the Urban Landscape in Brazil – Case Study of Balneario Camboriu - Marina Magalhães de Castro; Ana Clara Mourão Moura; Renata Nogueira Herculano; Tatiana de Aguiar; Francisco Henrique de Oliveira (Disegnare con, 2018)
In Brazil, urban morphometric parameterization has become the main instrument of urban planning. Parametric Modeling of the Urban Landscape presents itself, therefore, as an important methodological tool to the landscape planning and construction. It emerges as a possibility to aggregate the different dimensions that compose the urban landscape which are capable of measurement. Moreover, it enables the planning of large areas according to specific aspects, which can be then developed into macro-solutions and projects at the local level. In this work, a dynamic cartography based on the Parametric Modeling of the Urban Landscape methodology is used to represent the landscape proposed by Balneario Camboriu’s urban laws. DOI: https://doi.org/10.20365/disegnarecon.20.2018.17